Investigation of the Lactic Acid Bacteria in Kazak Cheese and Their Contributions to Cheese Fermentation - Li, Jie; Huang, Qian; Zheng, Xiaochun; Ge, Zhengkai; Lin, Ke; Zhang, Dandan; Chen, Yu; Wang, Bin; Shi, Xuewei (Frontiers in Microbiology, 2020)
Kazak cheese is a traditional dairy product fermented by lactic acid bacteria (LAB) in Xinjiang. To investigate the LAB in Kazak cheese and their contributions to cheese fermentation, four representative LAB, Streptococcus thermophilus B8, Lactobacillus helveticus B6, Weissella confusa B14, and Lactobacillus rhamnosus B10, were isolated from Kazak cheese and subsequently used to ferment cheeses, which were named StC, LhC, WcC, and LrC, respectively. The result showed that most of the physical and chemical indicators had no significant difference, except for moisture and fat. W. confusa B14 was beneficial to the production of amino acids, whereas S. thermophilus B8 promoted the formation of organic acids and contributed to formation ideal texture property. Furthermore, the four cheeses all possessed a strong fruity aroma, with brandy, sweet, herbaceous, pungent, and fatty aromas being the most prominent in WcC. This is because L. helveticus B6 produced a high concentration of hexanal, nonanal, octanal, 3-methylbutanoic acid, ethyl acetate, ethyl butanoate, isoamyl acetate, and ethyl hexanoate in LhC. Research on the fermentation mechanism of LAB in cheese will provide a theoretical basis for the quality control and industrial production of Kazak cheese.